Effects of institutional quality and the development of the banking system on corporate debt - Alvaro Edmundo Tresierra; Sergio David Reyes (Journal of Economics, Finance and Administrative Science, 2018)
This study aims to determine if the quality of national institutions and banking development condition the maturity of debt depending on the horizon of short or long term. Design/methodology/approach Analysis is performed on a sample of 116 nonfinancial companies from Peru and Brazil. The measures of quality of national institutions and banking development were obtained from World Bank data and included factorial analysis for dynamic considerations. Findings The findings, through the treatment of pointed indicators, the factor analysis and the subsequent estimation of a dynamic econometric model, called GMM-SYS, show that institutional quality fosters the maturity of long-term debt and banking development boots short-term financial relations. Research limitations/implications Evaluating different measures of the quality of national institutions and banking development is necessary to demonstrate the robustness of the results beyond the sample evaluated in Latin America. Practical implications The research allows to understand the interaction between national institutions and system banking through debt maturity, and this is useful for establishing common target between both groups. Social implications It is important for corporate finance to understand the mechanisms of the interaction between national institutions and system banking, because this affects internal decisions of firms regarding financial implications. Originality/value The treatment of measures of national institutions and banking development include dynamic considerations, and the application of this study in Latin America provides new findings regarding these kind of indexes and their interaction with firms' features such as debt maturity.
Keywords: 330; Stock market; Banking system; Factorial analysis; GMM-SYS; Institutionality; Maturity of debt